SPECIFICITY OF TRANSACTION COSTS AT BIOENERGY PRODUCERS – ACASE STUDY - Wojciech Ciechanowski; Mariusz Maciejczak; Łukasz Ściubak (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2022)
One of the nexus in the modern energy sector are bioenergy companies. To generate green electricity, economic operators trade in the market, incurring transaction costs. The main objective of the paper is to identify and describe the transaction costs using a case study of biomass combined heat and power plant (CHP). The company used for the case study was Polmos Żyrardów. A diagnostic survey with a questionnaire was carried out. It was found that information procurement and negotiation costs are the most significant in the transaction cost structure of a biomass CHP plant. The importance of access to information about biomass suppliers in the region and the company›s closest surroundings was highlighted the most. This factor significantly increases the time-consuming activities that make up the process of acquiring information about a potential business partner. The aspect of the formalisation of the contract and the building of mutual trust between the participants in the transaction were emphasised as elements to minimise the uncertainty and opportunism of the partners. It is argued that the level of transaction costs influences decision-making within the organisation, also translating into the efficiency of the entire biomass CHP area. Conscious management of energy resources and care for the environment has made Polmos Żyrardów self-sufficient in energy. In light of the challenges of the energy transition, bioenergy installations make an important contribution to reducing greenhouse gas emissions and building circular bioeconomy.